Trend, Cost of Production and Method of Sale of Arecanut in Kerala - N. Karunakaran (World Journal of Agricultural Sciences, 2013)
Arecanut is an important commercial crop of Kerala. During the past three decades, the arecanut cultivation underwent significant increase in area and production due to area effect and the yield effect. The input wise cost of arecanut cultivation in Kerala indicates increase in the cost of production by size of farm. Marketing system in Kerala include different type of markets, marketing channels and method of sale. In earlier times trade in arecanut was monopolistic in nature and has changed since the establishment of CAMPCO. In the state arecanut growers follow different methods of sale; majority of the farmers follow the method of selling arecanut to the traders in the village immediately after harvest. Arecanut marketing channel includes a number of market intermediaries like village traders, itinerant merchants, private wholesalers, retailers, co-operative depots, etc. Co-operative marketing is efficient in Kerala due to lower price spread and better price to the arecanut growers